1994
DOI: 10.1080/01422419408241243
|View full text |Cite
|
Sign up to set email alerts
|

Colour transparency: A novel test of QCD in nuclear interactions

Abstract: Colour transparency (CT) is a cute and indispensable property of Q C D as a gauge theory. C T tests of Q C D consist of production of the perturbatiue small-sized hadronic state and measuring the strength of its non-perturbatiue diflraction interaction in a nuclear matter. The energy dependence of the final-state interaction in a nuclear matter probes a dynamical evolution from the perturbatiue small-sized state to the full-sized nonperturbatiue hadron. Q C D observables of C T experiments correspond to a nove… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
5
0

Year Published

1994
1994
2001
2001

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 81 publications
0
5
0
Order By: Relevance
“…which makes this reaction an ideal laboratory for testing color transparency (CT) ideas (for the recent review on CT see [2,3]). In the exclusive production off nuclei, the nuclear attenuation effects were predicted [1] to be ∝ r 2 Q and vanish at large virtuality Q 2 of the photon, which was confirmed by the recent data on the ρ 0 production from the FNAL E665 experiment [4].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…which makes this reaction an ideal laboratory for testing color transparency (CT) ideas (for the recent review on CT see [2,3]). In the exclusive production off nuclei, the nuclear attenuation effects were predicted [1] to be ∝ r 2 Q and vanish at large virtuality Q 2 of the photon, which was confirmed by the recent data on the ρ 0 production from the FNAL E665 experiment [4].…”
mentioning
confidence: 99%
“…The cross section σ(r) has the CT property of vanishing at r → 0 [9,10]. Since the CT property is conveniently quantified in terms of σ(r) (for the review see [2,3]), it is important to understand how σ(r) is probed in the exclusive electroproduction.…”
mentioning
confidence: 99%
“…1b). Although SCHC diffraction excitation amplitudes are smaller than elastic ones (for suppression of diffraction excitation by the node effect see [30]), the inelastic (p, p * ) spin-flip transitions can be enhanced compared to elastic (p, p ′ ) ones [5]. Consequently, one can not exclude that the contribution of p * excitations would enhance the effective r 5 by a large factor.…”
Section: Numerical Estimates: Unitarity Driven G (U)mentioning
confidence: 99%
“…It was shown that CT and/or weak final-state interaction (FSI) in A(e, e ′ p) reactions arises from delicate cancellations of contributions from elastic (|i = |p ) and inelastic (|i = |p ) intermediate states |i propagating inside the nucleus [2,3]. At Q 2 ∼ < 7 (GeV/c) 2 the contributions from inelastic rescatterings is still small, however, and hence the very small signal in the NE18 experiment (for a general review on CT see [5][6][7]). Another very interesting aspect of the experiment is the evidence for substantial FSI effects already in the deuteron.…”
mentioning
confidence: 99%
“…(2) the factor exp t( b, z)ξ( ∆) in the integrand of Eq. (5) causes a broadening of the p ⊥ -distribution [6,8]:…”
mentioning
confidence: 99%